Market self-regulation and state planning of the economy in conditions of demand and resource limits - Bykau, Aliaksei A.; Khaustovich, Natallia A.; Parkhimenka, Uladzimir A. (Journal of the Belarusian State University. Economics, 2022)
The paper considers the possibility of applying the theory of resource-constrained and demand-constrained systems, to the description and resolution of problems of failures in the normal functioning of economic systems under external shocks. Such shocks include the consequences of COVID-19 and the lockdown, as well as sectoral sanctions applied to the Belarusian economy. The question of which of the economic systems, planned or market, is best able to withstand these shocks is analysed. As a first approximation, it is shown that the Keynesian and post-Keynesian concepts of economic regulation through demand stimulation do not allow to completely circumvent resource constraints.